Total Spectrum Power and Power of HF Waves in Athletes Depending on the Phase of the Training Year and Other Factors (Review) - Denis A. Kataev; Viktor I. Tsirkin; Vlada V. Kishkina; Svetlana I. Trukhina; Andrey N. Trukhin (Northern (Arctic) Federal University, 2024)
As part of the study into the nature of such heart rate variability (HRV) indicators as total spectrum power (TP), absolute power of high frequency waves (HFAP) and their relative power (as a percentage of TP (HF%)), literature data and the results of our own research on the values of these indicators in athletes are systematized. It has been established that TP, HFAP and HF% depend on the type of sports (reaching their maximum in endurance training), experience in sports (the higher the level, the higher these indicators), and phase of the training year (increasing during the preparatory phase, but decreasing slightly in the competitive phase and more significantly during the transition phase). In particular, the paper presents the results of the study of the first author of this article, elite skier D.A. Kataev, who recorded his own cardiointervalogram and the volume and intensity of daily training loads during one training year. This made it possible to evaluate TP, HFAP and HF% dynamics over the three phases and to establish that TP values are directly dependent on the volume and intensity of training loads. However, no such relationship was established for HFAP and HF%. It was shown that in 8 cross-country skiers (members of the Tatarstan national team) TP, HFAP and HF% values during the preparatory phase were higher than in the competition phase. The authors conclude that TP, HFAP and HF% values mainly reflect the influence of the parasympathetic division of the autonomic nervous system (ANS) on athletes' cardiac activity, as well as on the activation of the sympathetic division of the ANS during the development of precompetition emotional stress in the competitive phase. An idea is postulated about the formation of the anti-apoptotic myocardial system during endurance training, which includes antioxidants, dopamine, serotonin, acetylcholine, prostaglandins, nitric oxide and other compounds.